Thinking with Algorithms, Reading with Discernment: Artificial Intelligence, Critical Reading, and Academic Satisfaction in Accounting - Hinojosa-Salazar, Carlos Alberto; Fernández, Juan Manuel Buendía; Rios, Irma Dolores Montenegro; Servan, Segundo Ramon Salazar; Puerta, Carlos Andrés Rojas (Journal of Cultural Analysis and Social Change, 2025)
The study explores how the strategic use of artificial intelligence (AI), critical reading habits, and academic satisfaction are articulated among accounting students at UNTRM during the 2025-II semester. A quantitative, applied approach was used, under a non-experimental, cross-sectional, and correlational design. The sample, stratified by study cycles, consisted of 139 students from a population of 213. Three Likert-type questionnaires were used to measure strategic use of AI, critical reading, and academic satisfaction, which were subjected to content validation by expert judgment and internal reliability analysis. The results show predominantly high levels of strategic AI use and positive associations with critical reading and academic satisfaction, especially when both dimensions are in high ranges. These findings suggest that AI can become a valuable educational support when integrated as a complement to critical reading and not as a substitute, recognizing the limitations of a cross-sectional study based on self-reports.